2014
DOI: 10.5812/nms.18143
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nursing and Midwifery Students Competencies in Communication With Patients With Severe Communication Problems

Abstract: Background: Clients with communication impairment are at risk for health disparity. Hence, health care workers should be knowledgeable and skillful in communication. However, no studies are available on Iranian nursing and midwifery students' communication skills with patients with severe communication problems. Objectives: The present study was conducted to investigate Iranian nursing and midwifery students' competencies in communication with patients with severe communication problems. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Thus, nurses with elevated levels of resilience are more likely to possess strong communication skills and actively engage in patient care. (17,45) Fourthly, the mediation model revealed that resilience remarkably acted as a mediator in the relationship between EI and HCA. As per the pathway of EI → Resilience → HCA, it is crucial to develop strategies aimed at enhancing resilience among nursing postgraduates as a means to improve their HCA.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, nurses with elevated levels of resilience are more likely to possess strong communication skills and actively engage in patient care. (17,45) Fourthly, the mediation model revealed that resilience remarkably acted as a mediator in the relationship between EI and HCA. As per the pathway of EI → Resilience → HCA, it is crucial to develop strategies aimed at enhancing resilience among nursing postgraduates as a means to improve their HCA.…”
Section: Discussionmentioning
confidence: 94%
“…Recent research examining Deaf knowledge and awareness in the health care setting has included US medical students (Hoang et al, 2011), nurses in Greece ( n = 173; Velonaki et al, 2015), Iranian undergraduate ( n = 71) and nurse midwifery ( n = 22) students (Adib Hajbaghery & Rezaei Shahsavarloo, 2014), and a small sample of nurse practitioners in the United States ( n = 10; Pendergrass et al, 2017). The limited research to date examining Deaf culture knowledge among bedside nurses in the United States is concerning, given they are often the first point of contact for first point of contact for patients.…”
mentioning
confidence: 99%
“…Si las enfermeras entienden las necesidades, los pensamientos y los temores de los pacientes, y éstos sienten el cuidado de las enfermeras, entonces mejorará la calidad de vida de los pacientes Hafskjold et al, 2016). Por otra parte, las enfermeras con una gran capacidad de comunicación están más dispuestas a tomar la iniciativa de comunicarse con los demás y son capaces, por tanto de prestar unos cuidados enfermeros adecuados (Adib & Rezaei, 2014).…”
Section: Capítulo 5-discusión Y Conclusionesunclassified